ANALISIS PERHITUNGAN PENYUSUTAN ASET TETAP MENURUT PSAK 17 DAN UNDANG-UNDANG PAJAK SERTA DAMPAKNYA TERHADAP PENGHASILAN KENA PAJAK PADA PT.WANA ARTA MANUNGGAL - Leroy Lionel Yuhaniar (Jurnal Bina Akuntansi, 2019)
This study aims to determine how the calculation of depreciation of fixed assets inaccordance with IAS 17 and the Law - Tax Law as well as determine the impacton taxable income of both of these calculations. In this study the author usesdescriptive method is a method of analyzing the data which the data are collected,compiled, interpreted, and analyzed so as to produce a complete information andefficient in accordance with the title analysis of calculation of depreciation offixed assets according to IAS 17 and law - tax law and its impact taxable incomeat PT Wana Manunggal Arta ". The data collected is primary and secondary data.Using a variety of data collection techniques, such as interview techniques,observation techniques. The author has analyzed the fixed assets of the companyand it can be concluded that the company put on straight-line depreciationmethod to depreciate its fixed assets has been well implemented by the company.Application of the method of depreciation for tax purposes in accordance with theprovisions of the tax is less because there are weaknesses in its application.Depreciation expense based on commercial Rp 197,323,566 whereas according tothe fiscal depreciation expense amounting to Rp 169,967,624 was due todifferences in the method of depreciation according to tax provisions containedfiscal correction of the vehicles used for the company's operations and for theinventory of vehicles for employees.